2020
DOI: 10.3389/fped.2020.00046
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccination in Male and Female Adolescents Before and After Kidney Transplantation: A Pediatric Nephrology Research Consortium Study

Abstract: Background: Kidney transplant (KT) recipients have higher incidence of malignancies, including Human Papillomavirus (HPV)-associated cancers. Thus, HPV vaccines may have an important role in preventing HPV-related disease in this population; however, immunogenicity and safety data are lacking. Objective: To examine the immunological response and tolerability to HPV vaccination in pediatric KT recipients compared to future KT candidates. Methods: The quadrivalent HPV vaccine was administered to girls and boys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The observed seroconversion rates and GMTs in SOT patients are noticeably lower compared to data from 16 to 26 year old healthy adults [7][8][9][10]. So far, only four studies have reported the immunogenicity of HPV vaccines in SOT patients, and all concerned the qHPV vaccine [14,[26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…The observed seroconversion rates and GMTs in SOT patients are noticeably lower compared to data from 16 to 26 year old healthy adults [7][8][9][10]. So far, only four studies have reported the immunogenicity of HPV vaccines in SOT patients, and all concerned the qHPV vaccine [14,[26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…77 , and noted vaccine safety in all groups. 90,93 However, receipt of systemic immunosuppressive therapies was associated with significant decrease in seroconversion and geometric titers for each vaccine serotype tested; this difference was most apparent in the transplant recipient group with 69%-89% seroconversion. 93 Optimally, all efforts should be made to provide the 3-dose HPV vaccine series prior to transplantation.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…90,93 However, receipt of systemic immunosuppressive therapies was associated with significant decrease in seroconversion and geometric titers for each vaccine serotype tested; this difference was most apparent in the transplant recipient group with 69%-89% seroconversion. 93 Optimally, all efforts should be made to provide the 3-dose HPV vaccine series prior to transplantation. However, if unable to be completed, the remaining doses can be completed starting 3-6 months after transplant; although immunogenicity will be less robust post-SOT when compared with individuals pre-SOT or those who are not immunocompromised, there is an ongoing benefit.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
See 2 more Smart Citations